Cadeia Global de Valor de couro e calçados: Padr\~oes de inserç\~ao do Brasil, México e Taiwan - Synthia Kariny Silva de Santana (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The main objective of this paper is to provide for more and better evidence allowing the examination of Brazil's position within Global Value Chain on leather & footwear Industry. To do so, we analyzed the pattern of international integration in Taiwan and Mexico as remarkable experiences for the Brazilian footwear industry. Therefore, the issue of functional upgrading and governance structure within the GVC will be explored as well as the coordination and integration of different players within the industry.
Keywords: F14; F23; L23; L67; 330; Global Value Chain; leather footwear industry; fragmentation of production